Women’s Opinion about Women’s Rights regarding Family Planning in Hegarmanah Village, Jatinangor Subdistrict, West Java in 2013 - Suzanne Saw; Yoni Syukriani; A. Hussein S. Kartamihardja Kartamihardja (Althea Medical Journal, 2015)
Background: Universal Declaration of Human Rights stated that all mankind have equal right and dignity. Both woman and man have rights regarding family planning. It is often assumed that in developing country, women do not consider their rights in family planning decision making process. This study was carried out to determine the opinion of women regarding women’s rights in family planning.Methods: A descriptive study was carried out to 99 respondents during the period of August to October 2013, in Hegarmanah village, Jatinangor subdistrict. The inclusion criteria were women aged 15–49 years old, able to speak Bahasa Indonesia, and agreed to participate. Variables for this study were the opinions of the respondents regarding woman’s rights in family planning which were represented in 12 questions. Collected data were presented as percentages shown in tables.Results: Most of the respondents stated that they had the rights in family planning decision making, including choosing contraceptive methods, number of children, and spacing of each child. However, all of  the respondents agreed that men should be involved in it. More than half of the respondents stated that they asked opinion from family member regarding family planning especially their mothers. Cultural norms did not influence the family planning decision making. However, religion influenced the family planning decision making.Conclusions: Majority of the women in Hegarmanah village have the role to make decision on family planning by considering the opinions of their spouses, other family members, friends and their religions. DOI: 10.15850/amj.v2n3.526